The Implementation of Halal Product Assurance System at CV. Mamifood Sukses Abadi Bogor - Maulidian Maulidian; Moh. Taufik; Hermawan Seftiono (Universitas Djuanda, 2024)
Halal food is crucial for consumers, especially in Indonesia, which has the biggest Muslim population in the world. Halal food can be identified by a halal label on its packaging. Halal labels can be obtained through the Halal Product Assurance System (SPJH). This study evaluates the Halal Product Assurance System in CV. Mamifood Sukses Abadi Bogor, involving critical ingredients such as cheese sauce, cheese spread, and milk jam. The findings of this study suggest that CV. Mamifood Sukses Abadi Bogor is committed to and responsible for the implementation of the Halal Product Assurance System. All ingredients used for products have a halal certificate issued by the Institute for the Study of Food, Drugs, and Cosmetics of the Indonesian Ulema Council (LPPOM MUI). Its production has complied with the conditions regulated by the Halal Product Guarantee Agency (BPJPH). The name and sensory profile of the product does not link to the name and sensory profile of non-halal products. The top management has also conducted internal audits and management reviews, with the most recent one taking place in 2021, to monitor and evaluate the Halal Product Assurance System implementation. In general, CV. Mamifood Sukses Abadi Bogor has adhered to all of the Halal Product Assurance System criteria established by the Halal Product Guarantee Agency.